The First Report and Molecular Analysis of Enterocytozoon bieneusi from Raccoon (Procyon lotor) in North of Iran. (6th February 2020) - Javanmard, Ehsan; Nemati, Sara; Sharifdini, Meysam; Rostami, Ali; Mirjalali, Hamed; Zali, Mohammad Reza
Abstract: Microsporidia are known opportunistic microorganisms and usually transmitted via the fecal–oral route. However, there is no information about human‐infecting microsporidia in wildlife in Iran. This study aimed to investigate and analyze human‐infecting microsporidia isolated from raccoons in north of Iran. Totally, 30 fecal samples were collected; then, DNA extraction was performed and specific fragments of the SSU rRNA gene of Enterocytozoon bieneusi and Encephalitozoon species were amplified. After amplification and sequencing the ITS, the results were compared to the GenBank database. Phylogenetic trees and network analysis were employed to explore probable relationships. E. bieneusi was the only detected microsporidia among samples. Genotyping showed the genotypes D, E, and RA in 15/18 (83.33%), 1/18 (5.55%), and 2/18 (11.11%) of samples, respectively. Novel genotypes RA1 and RA2 grouped together and apart from other genotypes. E. bieneusi genotypes D and E clustered with the genotypes previously reported from animals, humans, and environmental samples. Network analysis revealed six distinct sequence types among raccoon's isolates. This study demonstrated that E. bieneusi genotype D was the most prevalent microsporidia among raccoons. It seems that wildlife may play a role in dispersion of microsporidia spores.